PENGARUH LINGKUNGAN FISIK,KUALITAS PRODUK,HARGA DAN PROMOSI PRODUK TERHADAPA KEPUASAN KONSUMEN ZEST CHICKEN SITUBONDO - Deyantoro Safian; Ika Wahyuni; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2025)
This study aims (1) To determine the effect of service quality, price and promotion variables partially on customer satisfaction variables at the Panarukan Cell Counter in Panarukan Situbondo (2) To determine the effect of service quality, price and promotion variables simultaneously on the Panarukan Cell counter variable in Panarukan Situbondo (3) To comply with the influence of service quality, price and promotion variables which have a dominant effect on Panarukan Cell Counters in Panarukan Situbondo. The method used is quantitative. The result of the research is the multiple linear regression equation Y = 8,079E-17 + 0,221X1 + 0,416X2 + 0,370X3 + e. Partially service quality has a positive effect with tcount 3,261> ttable 1,986 sig value 0,003 < 0,05, price indicates tcount 4.159 > ttable 1.986, sig value 0.000 < 0.05, promotion shows tcount 3.335 > ttable 1.986 sig value 0.002 < 0.05. Simultaneously, service quality, price and promotion have an effect on customer satisfaction with the value of Fcount 40.651 > Ftable 2.70. The variable that has the most dominant influence in this study is the price variable with a value of 4.159. R square 0.652 is greater than the service quality variable (X1) and the promotion variable (X3). Based on the coefficient of determination, it shows a value of 0.652 from these results, it means that all independent variables have a contribution of 65.2% to the dependent variable which has high influence and the remaining 34.8% is influenced by other factors not included in the study.